The application of patient-derived induced pluripotent stem cells for modeling and treatment of Alzheimer's disease. Issue 1 (March 2019) - Han, Fabin; Liu, Chuanguo; Huang, Jin; Chen, Juanli; Wei, Chuanfei; Geng, Xiwen; Liu, Yanming; Han, Dong; Li, Mengpeng
Alzheimer's disease (AD) is the most prevalent age-related neurodegenerative disease which is mainly caused by aggregated protein plaques in degenerating neurons of the brain. These aggregated protein plaques are mainly consisting of amyloid β (Aβ) fibrils and neurofibrillary tangles (NFTs) of phosphorylated tau protein. Even though the transgenic murine models can recapitulate some of the AD phenotypes, they are not the human cell models of AD. Recent breakthrough in somatic cell reprogramming made it available to use induced pluripotent stem cells (iPSCs) for patientspecific disease modeling and autologous transplantation therapy. Human iPSCs provide alternative ways to obtain specific human brain cells of AD patients to study the molecular mechanisms and therapeutic approaches for familial and sporadic forms of AD. After differentiation into neuronal cells, iPSCs have enabled the investigation of the complex aetiology and timescale over which AD develops in human brain. Here, we first go over the pathological process of and transgenic models of AD. Then we discuss the application of iPSC for disease model and cell transplantation. At last the challenges and future applications of iPSCs for AD will be summarized to propose cell-based approaches for the treatment of this devastating disorder.